Paths From Science Towards God : The End of All our Exploring - Peacocke, Arthur (Oxford Oneworld, 2002)
The author, a distinguished biochemist who serves as a priest in the Church of England, calls for for a bold new synthesis of science and religion. Only through such a new synthesis, he asserts, can Christianity regain the plausibility it has lost through centuries of futile resistance to scientific progress.
Include Index, Notes, Glossary and Map
Keywords: Religion and science